1991
DOI: 10.1016/1044-0305(91)80011-u
|View full text |Cite
|
Sign up to set email alerts
|

An automatic reaction control chemical ionization technique in ion trap detector for quantitative plasma profding of arecoline in treated alzheimer patients

Abstract: An automatic reaction control chemical ionization technique in an ion trap detector (lTD) was used to quantitate the levels of the cholinergic drug, arecoline, in plasma of treated patients with Alzheimer's disease. The chemical ionization reaction was carried out with acetonitrile. The protonated molecules of arecoline (m I z 156) and the internal standard, homoarecoline (m / z 170), were monitored. Human plasma samples were extracted with a readily evaporable solvent mixture, the residues reconstituted and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Acetonitrile CI is routinely used in environmental 71,72 and biochemical 73,74 trace analysis. It is also widely used in toxicology, for the detection of drugs such as benzodiazepines 15 and illicit drugs such as cocaine, 75 methadone 76 and lysergic acid diethylamide ("LSD").…”
Section: Because Of Their Low Proton Affinities Chemical Ionization mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetonitrile CI is routinely used in environmental 71,72 and biochemical 73,74 trace analysis. It is also widely used in toxicology, for the detection of drugs such as benzodiazepines 15 and illicit drugs such as cocaine, 75 methadone 76 and lysergic acid diethylamide ("LSD").…”
Section: Because Of Their Low Proton Affinities Chemical Ionization mentioning
confidence: 99%
“…77 Comparing methane and acetonitrile for the detection of arecoline in the treatment of Alzheimer disease, Shetty et al showed that acetonitrile chemical ionization permits hydride abstraction from arecoline that is observed with methane to be limited significantly. 73…”
Section: Because Of Their Low Proton Affinities Chemical Ionization mentioning
confidence: 99%
“…Acetonitrile (CH 3 CN, molecular weight (MW) = 41) is an unconventional liquid CI reagent first reported by Yinon and Cohen . It has been reported recently as a proton-transfer CI reagent for several environmental , and biological applications. With a proton affinity of 788 kJ/mol, acetonitrile is a slightly less energetic reagent than isobutane (proton affinity = 683 kJ/mol) .…”
mentioning
confidence: 99%
“…Oxymatrine treatment could reduce the serum levels of TNF‐α, IL‐6, and the expression of NF‐κB and ICAM‐1 in the colonic mucosa of rats with DSS‐induced colitis indicating that oxymatrine ameliorates colonic inflammation and thus alleviates diarrhoea and bloody stools (Zheng et al, ). In another study, an ion trap detector (ITD) was used to quantify the levels of the cholinergic drug arecoline in the plasma of patients with treated Alzheimer's disease; the protonated molecules of arecoline (m/z 156) and the internal standard, homoarecoline (m/z 170), were monitored (Shetty et al, ). The alkaloid baptifoline was also identified in an extract of Caulophyllum thalictroides rhizomes (Kennelly et al, ).…”
Section: Resultsmentioning
confidence: 99%